2008
DOI: 10.1111/j.1365-2958.2008.06461.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Form variation’ of the O12 antigen is critical for persistence of Salmonella Typhimurium in the murine intestine

Abstract: SummarySalmonella enterica subspecies I serotypes are responsible for the vast majority of salmonellosis in mammals and birds, yet only a few factors specific to this group that allow them to persist in this niche have been identified. We show that STM0557, a S. enterica subspecies I-specific gene encoding an inner membrane protein, is critical for faecal shedding and intestinal persistence of S. enterica serotype Typhimurium ATCC14028 in Salmonella-resistant mice, but mutations in this gene do not diminish sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 47 publications
8
110
0
Order By: Relevance
“…Finally, the genes SEN0535 and SEN0536 within SPI-16 also were negatively selected during S. Enteritidis infection of mice. We have shown previously that the orthologous genes in S. Typhimurium are responsible for the "form variation" of the O12 antigen to generate the 12-2 variant that is critical for the persistence of this serovar in the murine intestine (15).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the genes SEN0535 and SEN0536 within SPI-16 also were negatively selected during S. Enteritidis infection of mice. We have shown previously that the orthologous genes in S. Typhimurium are responsible for the "form variation" of the O12 antigen to generate the 12-2 variant that is critical for the persistence of this serovar in the murine intestine (15).…”
Section: Resultsmentioning
confidence: 99%
“…The isolates from two patients (patients 5 and 7) did not contain the virulence plasmid pSLT (18). Several virulence factors are known to play a role in fecal shedding or the carrier state, including genes encoding thin aggregative fimbriae (19), genes encoding the secreted effectors ShdA and MisL (20,21), and genes located on Salmonella pathogenicity island 16 that are responsible for O-antigen glycosylation (22). The isolates analyzed in this study were all found to carry these genes, but none of these genes carried mutations in isolates from the same patient, suggesting that no further adaptive changes in these genes occurred during carriage.…”
Section: Resultsmentioning
confidence: 99%
“…In many Gramnegative bacteria, the O-antigen is a critical determinant in resistance to serum killing (44). Although glucosylation does not appear to change this role in Salmonella and Shigella (43,45,46), other cellular properties are certainly impacted in a species-specific manner. In Shigella, glucosylation leads to greater invasion, which is correlated to enhanced function and exposure of the type 3 secretion system (43), and elevated acid tolerance (47).…”
Section: Discussionmentioning
confidence: 99%
“…In Shigella, glucosylation leads to greater invasion, which is correlated to enhanced function and exposure of the type 3 secretion system (43), and elevated acid tolerance (47). In Salmonella, glucosylation is associated with virulent isolates (48) but is not a stable property leading to antigenic (form) variation in the O serotype (45,46,49). Glucosylation is induced by exposure to macrophages, and although not required for invasion and systemic spread, it appears to enhance long term colonization (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation